Investigation of the properties of polyester blended knitted fabric dyed with luminescent dyes as a highly visible fabric - Marwa A. Ali; Khaled M. Seddik; Ahmed G. Hassabo; Nancy S. El-Hawary (Scientific Reports)
Abstract Recently, many challenges have emerged in the dyes and textile fields to keep pace with the needs of the modern era while achieving safety and comfort during usage. Where the fluorescent dye caused a major boom in the field of dyes and was used to paint many surfaces for exciting and to attract attention purpose. They were utilized on textiles, particularly those composed of synthetic materials employed in hazardous areas such as traffic roads, where they become more visible upon exposure to light. Therefore, this research aims to investigate the color fastness, physio-mechanical properties, and UV resistance of fabrics produced by knitting techniques from polyester blended with cotton or bamboo and dyed with fluorescence dyes as dispersing yellow and red dyes. The evaluation results of dyed fabrics pointed to the dispersed red dyes improved the physio-mechanical, comfortable and colorfastness properties of polyester/cotton samples compared to polyester/bamboo samples except bursting resistance, while the dispersed yellow dyes considerably enrich the ultraviolet protections of polyester/bamboo samples compared to polyester/cotton.